The effects of a complex yoga-based intervention on healthy psychological functioning - Koncz, Adam; Nagy, Eszter; Csala, Barbara; Körmendi, János; Gál, Vera; Suhaj, Csilla; Selmeci, Csongor; Bogdán, Ágota Selmeciné; Boros, Szilvia; Köteles, Ferenc (Frontiers in Psychology, 2023)
Background: Yoga based interventions were found to have a positive impact on various indicators of psychological functioning, such as perceived stress, satisfaction with life, positive and negative affectivity. Additionally, such interventions improved bodily or interoceptive awareness and spirituality. Methods: The present study assessed the effects of a 3-month long complex yoga-based intervention compared to a passive control group in a Hungarian community sample. The final sample consisted of 44 intervention (Mage =47.5, SD = = 8.76) and 29 control participants (Mage = 47.4, SD = 9.47). The aforementioned constructs were measured one week before and after the intervention. Results: The intervention reduced participants’ perceived stress (p = <.001, ηp2 = .153) and negative affectivity (p = .019, ηp2 = .113), improved spirituality (p = .048, ηp2 = .054) and various aspects of interoceptive awareness such as noticing (p = <.001, ηp2 = .169) attention regulation, (p = <.001, ηp2 = .211), self-regulation (p = .002, ηp2 = .190) body listening (p = .010, ηp2 = .097), trusting (p = .026, ηp2 = .070), but did not impact positive affectivity and satisfaction with life. Conclusion: A 3-months long complex yoga-based intervention has a positive impact on many aspects of healthy psychological functioning.